STRATEGI STRATEGI PENGEMBANGAN SUMBER DAYA MANUSIA DALAM MENGATASI STUNTING - Indah Agustin; Hasmawaty AR (Publik: Jurnal Manajemen Sumber Daya Manusia, Administrasi dan Pelayanan Publik, 2024)
This study aims to identify and analyze human resource development strategies in efforts to address stunting in Ogan Ilir Regency. The research method used is a qualitative approach with a SWOT analysis to evaluate strengths, weaknesses, opportunities, and threats in the stunting prevention program. Data were collected through observation, interviews, and documentation with posyandu cadres, village midwives, and PKK teams. The study results indicate that enhancing knowledge and education for the community about stunting can improve the effectiveness of prevention programs. The conclusion drawn is the need for increased synergy among stakeholders and the optimal use of available resources to minimize stunting risks.